(untitled) (Journal of Science and Technology, 2016)
Over a period of one year, five office buildings in Ghana have been studied and the occupants were interviewed to assess the operation and accessibility of system and system controls at their working environment. In all, 64 occupants were interviewed. The results show that occupants in office buildings have a strong urge to operate windows, even in air-conditioned buildings. Satis- faction in office environment was found to correlate with the flexibility of building systems, sys- tem controls and personalisation of workspace. In addition, to increase the efficiency of building systems, occupants need to be trained in the proper use of the facilities available at their work- spaces. The results of the evaluation serve to contribute to the process of refinement and im- provement in office buildings.